Lokalitas Arsitektur Tradisional Bali dan Konsep Tri Hita Karana Pada Gereja Katolik Paroki Roh Kudus Katedral Denpasar Pasca Renovasi - Desy Yuliastuti Ida Ayu Made; Ikaputra (Universitas Dwijendra, 2025)
Balinese Traditional Architecture is a cultural heritage that has developed from generation to generation and is built based on traditional rules, both written and oral. One of the main concepts in this architecture is Tri Hita Karana, which means